EVALUATION OF THE IMPACT IN FAMILY OF USERS OF THE SERVICE OF HE/SHE HELPS TO HOME - E. Medina, Manuel; Fernández, Joaquina; Fuentes, Marcelina; Hernández, Marcial; Pérez, Ramona; Trabajo Social, Grupo de alumnos de (Anales de Psicología / Annals of Psychology, 1998)
The problem of the aging is waking up restlessness as much in the Governments as among the investigators, and one of the aspects that more it worries it is the situation of the sick old men of long duration and those other ones that live alone or that its families cannot pay him the due, even attentions they have been created it programs of attention that offer domiciliary services, inside these services he/she is the Service of Help to Home that has the important objective of avoiding the I eradicate of the old men, the one that have to leave of their houses, providing them a series of domestic tasks, helping to the families in the hygiene and the user's personal cares and another type of tasks, however, in spite of having studied the process and development of this service, in this work an analysis is presented from the perspective of the relatives that you/they benefit of this benefit of direct form and insinuation. It is sought to measure the impact level that the service of help to home has provided them.